Comparative Analysis of Various Z-source Based Five Level Cascaded H-bridge Multilevel Inverter - C. R. Balamurugan; K. Vijayalakshmi (Bulletin of Electrical Engineering and Informatics, 2018)
Z-source based multilevel inverters are the recent topologies as they have boosting ability and near sinusoidal output waveforms. This paper proposes different inverter topologies such as Z-source multilevel inverter and quasi Z-source multilevel inverter. This paper also deals with switched inductor and improved switched inductor topologies with quasi Z-network. The proposed switched inductor system reduces the voltage stresses caused by capacitors, power devices and diodes. In addition to multilevel inverter advantages, the proposed configuration employs Z-source inverter advantages. The Z-source inverter as compared to the traditional inverter is less costly, less complex, more efficient and more reliable. The performance of the proposed configurations is analysed by varying passive elements in impedance network and is simulated in MATLAB/SIMULINK. Phase disposition (PD) pulse width modulation (PWM) technique is applied on the proposed configurations and performance parameters are measured by the fast Fourier transform FFT analysis. The object of this paper is to develop an inverter which is used for variable speed drives with increase in output voltage by eliminating transformer and filter circuit. The performance is checked with standared parameter of the inverter.